Hello Linux! AI and Linux Redefining the Everyday User Experience - Yocum, Hunter; Martino, Lukas; Zegarek, Peter; Blake, Jonathan; Kalinowski, Jesse; Jaiswal, Chetan (2025 IEEE World AI IoT Congress (AIIoT), 2025)
The Linux operating system is a powerful, open-source tool that maximizes a computer's potential. It offers advantages over Windows and Mac OS, including stability and reliability, allowing users to run their system for long periods without crashes, a key reason why Linux is the preferred choice for servers and critical applications. Additionally, Linux delivers exceptional performance without requiring high-end hardware. Its cost-effectiveness makes it an attractive choice, as most distributions are free. Linux also provides great customizability, enabling users to modify the graphical interface and back-end settings like networking and the kernel. Despite these strengths, Linux primarily caters to users with technical expertise. The average user struggles with a pre-installed Windows system, let alone installing programs via Linux Shell commands. Many users fear stepping into the Linux world due to its complexity. Hello Linux! bridges this gap using AI and a Large Language Model. This desktop chatbot allows users to input a request which generates a shell script that is executed for them, simplifying the Linux experience. Users are granted system control without deep technical knowledge. Voice-activated commands further enhance accessibility, empowering those who struggle with typing. Most powerfully, Hello Linux! grants kernel-level access to the users at the press of a button. It creates job opportunities for individuals with disabilities and those familiar with computing but not terminal shell commands. In the future, Hello Linux! could be integrated into a Linux distribution, evolving user interaction and accessibility across the operating system.